Gunshot residue and airbags: Part I. Assessing the risk of deployed automotive airbags to produce particles similar to gunshot residue. Issue 2 (3rd April 2018) - Laflèche, Denis J. N.; Brière, Serge J. J.; Faragher, Nichole F.; Hearns, Nigel G. R.
Abstract: A criminal investigation prompted us to assess the risk that a random automotive airbag from a vehicle available in Canada may produce particles similar to inorganic gunshot residue (GSR) if deployed. We analyzed residues collected from 53 separate airbags, surveying 28 different vehicle makes and models, spanning the years 1993–2011. Of the 53 residues analyzed only two passenger-side airbags tested positive for GSR-similar particles containing lead, barium and antimony (PbBaSb). GSR-similar PbBaSb particles from the two positive airbags also incorporated either cobalt or fluorine, thus providing a chemical marker for elimination. Our findings reaffirm that while passenger side airbags can potentially be a non-firearm source of GSR-similar particles, careful inspection of element composition can identify particles uncharacteristic of conventional firearm discharge residue. RÉSUMÉ Une enquête criminelle nous a incités à évaluer le risque qu'un coussin gonflable déployé suite à une collision frontale d'un véhicule puisse produire particules similaires aux résidus de tir inorganiques (RT). Nous avons analysé des résidus de 53 coussins gonflables différents, provenant de 28 différents marques et modèles de véhicules, s'échelonnant de 1993 à 2011. Des 53 résidus sondés, seulement deux coussins du tableau de bord (côté passager) contenaient des particules avec du plomb, du baryum et de l'antimoine (PbBaSb). Ces deux particules contenaient cependant aussi du cobalt ou du fluor, permettant ainsi l'identification d'un marqueur pour fins d'élimination. Nos résultats réaffirment que bien que les coussins gonflables du tableau de bord (côté passager) peuvent être une source potentielle de RT, une inspection minutieuse de la composition élémentaire de ceux-ci peuvent trouver des particules non caractéristiques d'une décharge d'arme à feu conventionnelle.